Genetic analysis of a hereditary factor XII deficiency pedigree of a consanguineous marriage due to a homozygous F12 gene mutation: Gly341Arg. Issue 5 (28th May 2017) - Cheng, Xiaoli; Yang, Lihong; Huang, Guoyong; Jin, Yanhui; Hao, Xiuping; Wang, Mingshan
ABSTRACT: Objective and Importance: To study the gene mutations of factor XII (FXII) in a Chinese family of consanguineous marriage with FXII deficiency and illuminate the possible molecular pathogenic mechanism. It will contribute to our comprehension of the pathogenesis of the disease. Clinical presentation: The proband was a 26-year-old Chinese pregnant woman who was discovered, in a pregnancy test, with a prolonged activated partial thromboplastin time (APTT) at 61.6s (reference range, 29.0–43.0s). Techniques: The FXII activity (FXII:C) and FXII antigen (FXII:Ag) were tested with clotting assay and ELISA, respectively. The FXII gene ( F12 ) was ampliﬁed by PCR with direct sequencing. A ClustalX-2.1-win and four online bioinformatics software (PolyPhen-2, PROVEAN, SIFT, and Mutation Taster) were used to study the conservatism and harm of the mutation. The reference range of each test indicator in our laboratory was established with 150 healthy subjects. Conclusion headings: The FXII:C and FXII:Ag of the proband were 12% and 10% (normal range, 72–113%), respectively. Gene sequencing detected a homozygous c.1078G > A point mutation in exon 10 resulting in a substitution of glycine 341 by arginine (Gly341Arg) in the proline-rich domain of FXII. Family study showed that her elder brother had the same phenotype and genotype with her. In addition, there were another six heterozygous members in her family. Both conservatism and bioinformatics results indicated the mutation probably had affected the function of the protein. We thought the Gly341Arg mutation was responsible for the decreased activity of FXII:C and FXII:Ag. And in vitro expression experiment is performed to elucidate the precise pathological mechanism of the mutation.